1999
DOI: 10.1046/j.1365-2133.1999.03107.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to gold in gold sodium thiomalate-induced dermatosis

Abstract: Gold compounds are widely used in the treatment of rheumatoid arthritis. Mucocutaneous side-effects leading to the discontinuation of medication are common with these drugs. We investigated whether allergic mechanisms are involved in dermatosis induced by gold sodium thiomalate (GSTM). Thirteen gold dermatosis patients, 15 arthritis patients without any side-effects from GSTM and 11 healthy controls participated in the study. Venous blood lymphocytes from these subjects were cultured with GSTM and gold sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
1
11
0
1
Order By: Relevance
“…A roughly 90-fold range of values between rash-affected areas in different patients indicated that the absolute concentrations of gold were not directly related to rash initiation and that the mechanisms precipitating the development of skin rashes were probably not strictly dose dependent [3]. Based on studies with RA patents without side effects from gold sodium thiomalate, gold dermatosis patients, and healthy controls, authors concluded that gold dermatosis was mediated, in part, by allergic mechanisms; the lymphocyte proliferation test was recommended in the diagnosis of gold dermatosis [55].…”
Section: Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…A roughly 90-fold range of values between rash-affected areas in different patients indicated that the absolute concentrations of gold were not directly related to rash initiation and that the mechanisms precipitating the development of skin rashes were probably not strictly dose dependent [3]. Based on studies with RA patents without side effects from gold sodium thiomalate, gold dermatosis patients, and healthy controls, authors concluded that gold dermatosis was mediated, in part, by allergic mechanisms; the lymphocyte proliferation test was recommended in the diagnosis of gold dermatosis [55].…”
Section: Dermatitismentioning
confidence: 99%
“…Adverse side effects included skin rashes; protein in the urine; inflammation of the mouth; reduction in the number of circulating leukocytes; decreased number of blood platelets; aplastic anemia due to organ damage; lung abnormalities; adverse immune reactions, such as stomatitis, eosinophilia, lymphadenopathy, hypergamma globulinemia; severe hypotension, angina, myocardial infarction, nephrotoxicity and nephrotic syndrome; hepatitis; colitis; and chrysiasis (pigmentation) of the cornea, lens, and skin [3,8,14,44,50,52,53,57]. The most common side effect of chrysotherapy was skin toxicity, accounting for up to 60 % of all adverse reactions, especially lichenoid eruptions and non-specific dermatitis [3,47,54,55]. When chrysotherapy was discontinued, it was usually due to adverse mucocutaneous side effects during the first 2 years, and inefficacy after 4 years [56].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Drug-specific T cells may orchestrate the inflammatory skin reaction through release and induction of different cytokines. 5 Accordingly, T-cellemediated sensitization to drugs may be assessed in vitro by assays based on cytokine release from peripheral blood lymphocytes, such as macrophage migration inhibitory factor, 9,10 interferon gamma, [11][12][13][14][15][16][17][18][19][20][21] interleukin (IL)-5, 22,23 or other cytokines.…”
mentioning
confidence: 99%
“…Bei zwei von 15 Rheuma-Patienten ohne Hautsymptomatik und bei einer von elf gesunden Kontrollpersonen lieferte der LTT ein falschpositives Ergebnis. Im Epikutantest reagierte nur einer von 13 Patienten mit Hautsymptomatik und keiner aus den beiden anderen Gruppen positiv auf 0,5%iges Natriumdithiosulfatoaurat(I) in Vaseline (Räsänen et al 1999). Ein LTT mit Tetrachlorogold(III)säure (in einem Konzentrationsbereich zwischen 1 und 30 mg/ml) war bei 13 von 17 Patienten positiv, die eine Golddermatitis infolge der Rheumabehandlung entwickelt hatten.…”
Section: In-vitro-untersuchungenunclassified